Mindfully Green and Healthy: An Indirect Path from Mindfulness to Ecological Behavior - Geiger, Sonja M.; Otto, Siegmar; Schrader, Ulf (Frontiers in Psychology, 2018)
This paper examines the nature of the link between mindfulness and ecological behavior. Based on the notion that mindfulness incorporates heightened awareness of bodily sensations, we suggest an indirect path from mindfulness to ecological behavior that is mediated through individual health behavior, such as improved nutrition and increased exercise. This indirect path is corroborated with two online studies (n = 147/ n = 239) where mindfulness, personal health behavior and ecological behavior were assessed. We conclude that increased mindful awareness of momentary experience indeed favours more healthy lifestyles, which in turn relate to increased ecological behavior beyond personal health benefits. The findings support an agreeableness of personal and planetary health behavior and open up a path for environmental educational interventions based on mindfulness practices and personal health gains.